Chagas Disease across Contexts: Scientific Knowledge in a Globalized World. Issue 6 (18th August 2021) - Levin, Luciano G.; Kreimer, Pablo R.; Jensen, Pablo
ABSTRACT: Chagas is the most important endemic disease in Latin America. It was progressively constructed as a relevant public issue, starting as a medical problem, focusing later on housing conditions, poverty, or vector agents. In recent decades, research has mainly focused on the parasite's biological characterization. In the meanwhile, both Chagas disease and knowledge about it spread out geographically. We analyze the worldwide scientific production on Chagas, showing that countries' research strategies depend on two main factors: endemicity and research traditions. This approach complements previous studies, allowing us to better understand the construction of Chagas disease as a social and scientific problem.